Three human establishments / translated by Eulie Chowdhury - Corbusier, Le. (Punjab, 1979)
Every country in the third World is striving extremely hard to quicken its rate of growth through modernisation of agricultural practices and rapid indust rialisation. The pursuit of the goal of speedy economic development has disturbed the centuries old rural-urban relationship, as evidenced by the rapid and totally haphazard urbanisation of developing countries. The situation has been aggra vated further as a result of the enormous increase in the population of the less developed countries, leading to the emergence of vast slums, squatter colonies and sub-human living conditions. The natural environment having been disturbed beyond repair, we have been faced with grave problems of pollution which are contributing to sickness, depravity and despair.